Impacts of urbanization on land use change and its incidences on the climate: Case of Bingerville City (Ivory Coast, West Africa) - Kinanlie Sandrine Traore; Salomon Obahoundje; Asseypo Célestin Hauhouot; Arona Diedhiou (AIMS Geosciences)
This study aimed to assess the impact of urbanization on land use dynamics and its consequences on the local climate of the town of Bingerville for the period from 1990 to 2020. Land cover classification was based on Landsat data for the years 1990, 2000, 2015, and 2020 in order to perform a diachronic analysis of surface conditions. Precipitation and temperature data were used to assess local climate trends. A number of extreme precipitation indices (PRCPTOT, RR1, SDII, CWD, CDD, R95p, and R99p) and temperature indices (TN10p, TN90p, TX10p, TX90p, and WSDI) were calculated. The results show a sharp increase in the built-up area from 1990 to 2020, with 32.11 km2 (29.68% per year), compared with forest or crops, i.e., 19.09 km2 (0.62% per year), and scrubland or fallow land, i.e., 13.21 km2 (1.39% per year). However, extreme precipitation indices such as annual precipitation (PRCPTOT), rainy days (RR1), consecutive rainy days (CWD), and extremely rainy days (R99p) have increased from 2011 to 2020. In addition, buildings are correlated with RR1 and CWD. This could be one of the key factors contributing to the occurrence of flooding in the town of Bingerville, which is probably linked to urbanization. As for extreme temperature indices, most show a statistically insignificant trend, except for cold days (TX10p) and hot days (TX90p), which have a statistically significant trend of 0.004 and 0.018, respectively. This means that there have been changes in these two indices. Consecutive hot days (WSDI) and TX90p increased from 2010 to 2016, and buildings also correlated with these two indices. Consequently, changes in land use could have an influence on local temperature through the urban heat island (UHI) phenomenon. However, uncontrolled urbanization has an impact on the local climate. The town authorities need to be aware of this, and be rigorous in this area, to avoid future disasters in Bingerville.